Tolosa-Hunt Syndrome: Appraising the ICHD-3 beta diagnostic criteria. (September 2018) - Mullen, Evan; Green, Mark; Hersh, Eliza; Iloreta, Alfred-Marc; Bederson, Joshua; Shrivastava, Raj
Introduction: The term Tolosa-Hunt Syndrome was first used more than half a century ago to describe painful ophthalmoplegia accompanied by cranial nerve palsies. In the decades since, its diagnostic criteria have evolved considerably. The beta version of the 3rd Edition of the International Classification of Headache Disorders narrows these criteria to require the demonstration of granulomatous inflammation on MRI or biopsy. We believe this may introduce challenges to accurate diagnosis. Discussion: Requiring the demonstration of granulomatous inflammation for a diagnosis of Tolosa-Hunt Syndrome may introduce the potential for false negative and false positive diagnoses. Although the disorder presents secondary to granulomatous inflammation, MRI technology may not be able to identify it reliably, and biopsy is not always indicated for its symptomatology. Additionally, several cases have been reported of Tolosa-Hunt Syndrome diagnosed with MRI-confirmed granulomatous inflammation that later prove to be attributable to other pathologies. The emphasis on neuroimaging may therefore exclude some true Tolosa-Hunt Syndrome cases and include others resulting from other latent pathologies that are not visible on MRI. Conclusion: We wish to offer several potential modifications to the International Classification of Headache Disorders guidelines for Tolosa-Hunt Syndrome, including making the demonstration of granulomatous inflammation on MRI or biopsy non-mandatory and lengthening patient follow-up to two years for cases in which MRI is unrevealing.